Investigation Into an Outbreak of Dengue-like Illness in Pernambuco, Brazil, Revealed a Cocirculation of Zika, Chikungunya, and Dengue Virus Type 1. Issue 12 (March 2016) - Pessôa, Rodrigo; Patriota, João Veras; Lourdes de Souza, Maria de; Felix, Alvina Clara; Mamede, Nubia; Sanabani, Sabri S.
Abstract : Abstract: In April 2015, an outbreak of dengue-like illness occurred in Tuparetama, a small city in the northeast region of Brazil; this outbreak was characterized by its fast expansion. An investigation was initiated to identify the viral etiologies and advise the health authorities on implementing control measures to contain the outbreak. This is the first report of this outbreak in the northeast, even though a few cases were documented earlier in a neighboring city. Plasma samples were obtained from 77 suspected dengue patients attending the main hospital in the city. Laboratory assays, such as real-time reverse transcription polymerase chain reaction, virus cDNA sequencing, and enzyme-linked immunosorbent assay, were employed to identify the infecting virus and molecular phylogenetic analysis was performed to define the circulating viral genotypes. RNA of Zika virus (ZIKV) and Dengue virus (DENV) or IgM antibodies (Abs) to DENV or chikungunya (CHIKV) were detected in 40 of the 77 plasma samples (51.9%). DENV was found in 9 patients (11.7%), ZIKV was found in 31 patients (40.2%), CHIKV in 1 patient (1.3%), and coinfection of DENV and ZIKV was detected in 2 patients (2.6%). The phylogenetic analysis of 2 available partial DENV and 14 ZIKV sequences revealed the identities of genotype 1 and the Asiatic lineage, respectively. Consistent with recent reports from the same region, our results showed that the ongoing outbreak is caused by ZIKV, DENV, and CHIKV. This emphasizes the need for a routine and differential diagnosis of arboviruses in patients with dengue-like illness. Coordinated efforts are necessary to contain the outbreak. Continued surveillance will be important to assess the effectiveness of current and future prevention strategies.